2018
DOI: 10.1038/s41598-018-22875-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ugi-Azide Four-Component Reaction Products for Broad-Spectrum Influenza Antivirals with a High Genetic Barrier to Drug Resistance

Abstract: Influenza viruses are respiratory pathogens that are responsible for seasonal influenza and sporadic influenza pandemic. The therapeutic efficacy of current influenza vaccines and small molecule antiviral drugs is limited due to the emergence of multidrug-resistant influenza viruses. In response to the urgent need for the next generation of influenza antivirals, we utilized a fast-track drug discovery platform by exploring multi-component reaction products for antiviral drug candidates. Specifically, molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 41 publications
1
36
0
1
Order By: Relevance
“…During the preparation of this manuscript, a study reporting the identification of a new PA-PB1 inhibitor of influenza virus as well as the evaluation of the barrier to drug resistance of this compound was published (Zhang et al, 2018). In keeping with our findings, Zhang and coworkers showed that OST rapidly induced the selection of resistant viral variants, while no viruses with altered susceptibility to the PA-PB1 inhibitor were isolated.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…During the preparation of this manuscript, a study reporting the identification of a new PA-PB1 inhibitor of influenza virus as well as the evaluation of the barrier to drug resistance of this compound was published (Zhang et al, 2018). In keeping with our findings, Zhang and coworkers showed that OST rapidly induced the selection of resistant viral variants, while no viruses with altered susceptibility to the PA-PB1 inhibitor were isolated.…”
Section: Discussionsupporting
confidence: 77%
“…In keeping with our findings, Zhang and coworkers showed that OST rapidly induced the selection of resistant viral variants, while no viruses with altered susceptibility to the PA-PB1 inhibitor were isolated. However, they stopped the selection process at P10 (Zhang et al, 2018), while we carried out a prolonged drug-resistance selection for a total of 20/30 viral passages. Altogether, our data and the results obtained by Zhang et al suggest that drug resistance in vitro to dissociative inhibitors targeting the PA-PB1 interactions of influenza virus RdRP appears hard to develop, differently from what happens with the current anti-influenza drugs such as adamantanes and neuraminidase inhibitors and also with PA and PB2 enzymatic inhibitors approved or under clinical development (Hay et al, 1985;Molla et al, 2002;McKimm-Breschkin et al, 2012;Byrn et al, 2015;Noshi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations